Thymic bleeding after blunt chest trauma in a child - Aydin, Ayse Murat; Balci, Akin Eraslan; Birisik, Yasar; Ozercan, Ibrahim Hanifi; Sarac, Mehmet (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2015)
Trauma to the pediatric chest, occurring in isolation or with polytrauma, may result in a variety of injuries from minor to life-threatening. Trauma is the first cause of mortality in children over the age of one in industrialized countries. Injury to the thymus and thymic blood vessels is described in rare cases. A nine-year-old male patient was admitted to the emergency department after a traffic accident. The patient was followed up in the pediatric surgery intensive care unit due to the life-threatening condition. Patient had mediastinal widening due to blunt chest trauma. Contrast-enhanced chest computed tomography revealed mediastinal hematoma. A diagnosis of thymic bleeding was established in the operation.
Keywords: Chest trauma; child; imaging; thymic bleeding